The Development of Self‐Emulsifying Oil‐in‐Water Emulsion Adjuvant and an Evaluation of the Impact of Droplet Size on Performance. Issue 4 (19th January 2015) - Shah, Ruchi R.; Dodd, Stephanie; Schaefer, Mary; Ugozzoli, Mildred; Singh, Manmohan; Otten, Gillis R.; Amiji, Mansoor M.; O'Hagan, Derek T.; Brito, Luis A.
<x xml:space="preserve">Abstract</x> Microfluidization is an established technique for preparing emulsion adjuvant formulations for use in vaccines. Although this technique reproducibly yields high‐quality stable emulsions, it is complex, expensive, and requires proprietary equipment. For this study, we developed a novel and simple low shear process to prepare stable reproducible emulsions without the use of any proprietary equipment. We found this process can produce a wide range of differently sized emulsions based on the modification of ratios of oil and surfactants. Using this process, we prepared a novel 20‐nm‐sized emulsion that was stable, reproducible, and showed adjuvant effects. During evaluation of this emulsion, we studied a range of emulsions with the same composition all sized below 200; 20, 90, and 160 nm in vivo and established a correlation between adjuvant size and immune responses. Our studies indicate that 160‐nm‐sized emulsions generate the strongest immune responses. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1352–1361, 2015